Colorectal cancer (CRC) in young, black South Africans: a Morphological, Immunohistochemical and Molecular study - Cronje, Leandra (My University, 2007)
Background: Amongst black and white patients a disproportionately large number of young blacks present with colorectal cancer (CRC) in South Africa. We proposed that the comprehensive morphological and molecular analysis of a subset of cases might link them to the features associated with either the so-called “serrated pathway” or the hereditary pathway. Such an analysis could direct the diagnosis and treatment of similar patients in an effort to improve prognosis. Materials and Methods: Pathological review of 1732 cases and molecular analysis on a subset of these cases were retrospectively investigated, without knowledge of family history. Determination of the CpG island methylator phenotype (CIMP) was performed at five loci (methylated in tumour loci MINT1, 2 and 31, and the promoter region of the hMLH1 and MGMT genes) using methylation-specific PCR. Microsatellite status was determined through a multiplex PCR process involving the 5 loci specified by the National Cancer Institute. BRAF and KRAS gene status was determined by real-time PCR. Results: Eighty five percent of young patients (<50 years) were black (p < 0.000), predominantly male (56%; p = 0.026) with proximal tumours (25%; p = 0.064). These patients showed significantly more poorly differentiated tumours (p = 0.001) and extracellular mucin (p = 0.006). Molecular analysis revealed young blacks tended to present with loss of protein expression of the mismatch repair (MMR) proteins hMLH1, hMSH2, hMSH6 and MGMT, which resulted in a low MSI status. Overall methylation phenotype in these patients was low, together with the incidence of mutant KRAS genotype. Young white patients less frequently showed loss of mismatch repair protein expression, but MSI-H resulted from hMLH1 promoter hypermethylation in association with KRAS gene mutations and wild-type BRAF although this phenomenon may relate to the small numbers available for study. Conclusion: Many young black patients may develop CRC through the accumulation of mutations due to MSI that resulted from loss of MMR protein expression. These features are associated with hereditary nonpolyposis colorectal cancer (HNPCC). In contrast, young white patients in this series presented with features reminiscent of sporadic CRC characterized by high levels of CIMP and MSI that results from promoter methylation of the hMLH1 gene, as may be identified in the serrated neoplasia pathway.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirement for the degree of Doctor of Philosophy
Keywords: South Africa; Colorectal Neoplasms; Molecular Medicine; Phenotype